1984
DOI: 10.1080/03610738408258562
|View full text |Cite
|
Sign up to set email alerts
|

Age and field independence among women

Abstract: Age and the relationship to field independence, as measured by the Embedded Figures Test (EFT), among a sample of 160 creative women was studied. Comparisons were made between the mean EFT scores of creatine women and the mean scores of a sample of women not selected for creativity and the mean scores of two samples of men. Creative women were shown to be more field independent than women not selected for creativity and as field independence as two samples of younger men. A small but significant correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…As age and years in nursing increased, the Group Embedded Figures Test scores decreased or subjects scored more global in perceptual style. This has also been reported by Cionini, et al (1979), Larsen (1982), and Crosson (1984). These and other studies suggest that as persons grow older, they score as more field dependent.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As age and years in nursing increased, the Group Embedded Figures Test scores decreased or subjects scored more global in perceptual style. This has also been reported by Cionini, et al (1979), Larsen (1982), and Crosson (1984). These and other studies suggest that as persons grow older, they score as more field dependent.…”
Section: Discussionsupporting
confidence: 64%
“…Table 5 shows the Pearson correlations among ages, Group Embedded Magaro, and Velecogna (1979), Larsen (1982), and Crosson (1984).…”
Section: Resultsmentioning
confidence: 99%
“…FI individuals perform better on spatial ability tests, resulting in a higher overall IQ compared with FD individuals. Older people are more field dependent than younger people (e.g., Crosson 1984), even if general intelligence is controlled for (see Panek 1985). As originally reported by Witkin et al (1962), there is also evidence that men are more field independent than women (e.g., McLeod 1987).…”
Section: Managerial Implicationsmentioning
confidence: 85%
“…Karp (1967) and Crosson (1984) described a consistent increase of field dependent cognitive style among older adults. Markus and Nielsen (1963), studying the concept of field dependency among older adults, found that age is positively associated with a field dependent cognitive style.…”
Section: Cognitive Style and Everyday Problem Solvingmentioning
confidence: 88%